2020
DOI: 10.1111/are.14834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa oleifera leaf powder on skin mucosal immune responses and growth performance of guppy, Poecilia reticulata (Peter, 1860)

Abstract: The present study was carried out to evaluate the effects of moringa leaf powder through dietary supplementation in guppy fish (Poecilia reticulata) on skin immune responses and growth performance. A total number of 240 fish (average body weight of 0.13 ± 0.01 g) were equally divided into four feeding groups including 0% (T0), 5% (MT1), 10% (MT2) and 15% (MT3) concentration of moringa leaf powder. The results showed that levels of lysozyme activity and alternative complement activity (ACH50) significantly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
(21 reference statements)
2
6
0
Order By: Relevance
“…This increasing response is likely correlated with the antibacterial properties of M. oleifera due to its high content of several immune-stimulant bioactive components like carotenoids, moringinine, vitamins, minerals, sterols, alkaloids, flavonoids, caffeoylquinic acids, and phytoestrogens ( 41 , 46 ). Our results agreed with ( 22 , 46 , 47 ) findings that reported increasing lysozyme activities with increasing moringa levels in the diet.…”
Section: Discussionsupporting
confidence: 93%
“…This increasing response is likely correlated with the antibacterial properties of M. oleifera due to its high content of several immune-stimulant bioactive components like carotenoids, moringinine, vitamins, minerals, sterols, alkaloids, flavonoids, caffeoylquinic acids, and phytoestrogens ( 41 , 46 ). Our results agreed with ( 22 , 46 , 47 ) findings that reported increasing lysozyme activities with increasing moringa levels in the diet.…”
Section: Discussionsupporting
confidence: 93%
“…MO has been demonstrated to enhance the growth performance of common carp (Cyprinus carpio) [35] and O. niloticus [28], and FMO has been reported to increase the growth performance of C. gibelio juveniles [9]. In this study, supplementation with MO and FMO had no negative effects on the growth performance of M. amblycephala juveniles, which was consistent with previous studies on guppy (Poecilia reticulata) [36] and O. niloticus [37]. These discrepancies may be attributed to differences in fish size and feeding conditions, as well as fish species [28].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, Abd El‐Gawad et al (2020) illuminated that supplementing the powder of M. oleifera in diets also increased LYZ activities and IgM values of Nile tilapia. Furthermore, it was found that M. oleifera leaf powder significantly increased LYZ activities and ACH50 in skin mucous and plasma total immunoglobulins in treated guppies (Bisht et al, 2020). The enhancement of the serum immunological assays of Nile tilapia fed on MOL‐enriched diets may be correlated with several factors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dietary M. oleifera leaf extract can boost the immunological responses of gilthead seabream ( Sparus aurata ) (García‐Beltrán et al, 2020; Mansour et al, 2020), O. niloticus (Abd El‐Gawad et al, 2020; Monir et al, 2020) and also improve the survival rates of Mozambique tilapia ( Oreochromis mossambicus ) infected experimentally with Aeromonas hydrophila (Mbokane & Moyo, 2018). Furthermore, M. oleifera leaf powder can augment the skin mucosal immunity indices of guppies ( Poecilia reticulata ) (Bisht et al, 2020). Of interest, M. oleifera ‐based meals could strengthen the antioxidant status (Ahmed et al, 2020; Monir et al, 2020) and diminish the effects of physical stressors affecting fish (Elabd et al, 2019).…”
Section: Introductionmentioning
confidence: 99%